KOMBINASI ROLL DAN BALL MILL REFINER PADA PROSES CONCHING DALAM PEMBUATAN COKELAT BERBAHAN COCOA BUTTER SUBSTITUTE - Hasrul Abdi Hasibuan (Department of Agroindustrial Technology, Bogor Agricultural University, 2015)
This study was developed with respect to combination of roll and ball mill refiner on conching processon bench scale (10 kg/batch) with the aim of testing the manufacture of milk chocolate made ofcocoa butter substitute. The combination of these two refiner toolswere don eat the same time to soften the chocolate materials as they were related to the time of processing and quality of product. Performance evaluation of conching machine using a combination of roll and ball mill refiner was compared tothat without the ball mill refiner. The results showed that the combination of roll and ball mill refiner provided better quality with particle sizes meet the standard (<20 µm) and contaminant of iron (Fe) still received. The minimum time for production of chocolate at 10 kg/batch with a combination of roll and ball mill refiner was 60 hr, where as without the ball mill refiner it could be up to 100 hr, giving particle size according to standard. Thus, the combination of roll-ball mill refiner can be use as an alternative tool for the manufacture of chocolate on a bench scale.Keywords: ball mill refiner, cocoa butter substitute, chocolate, conching, roll refiner